Analisis Komunkasi Persuasif dalam Dakwah Ustdzah Oki Setiana Dewi Melalui Akun Tiktok - Alifia Nindi; Safitri Safitri; Adhi Kusuma (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Persuasive communication is a method of delivering messages that aims to influence the attitudes and behavior of the audience in a subtle and convincing manner. In the context of preaching, this approach is important so that religious messages can be well received by modern society, especially on social media. Ustadzah Oki Setiana Dewi as one of the Indonesian Muslim figures who actively preaches through the TikTok platform uses a persuasive communication style in conveying Islamic teachings. This study aims to examine how Ustadzah Oki Setiana Dewi applies persuasive communication in her preaching through her TikTok account. The method used is descriptive qualitative with a content analysis approach. The results of the study show that Ustadzah Oki Setiana Dewi uses persuasive communication strategies such as building empathy, using everyday language, and strengthening personal narratives to get closer to the audience. In addition, attractive video visualizations and relaxed delivery make the preaching message easier to understand and accept by the wider community.